Effect of Performance Assessment and Compensation on Lecturer and Employee Productivity in The Faculty of Education and Science North Sumatera Islamic University - Siregar, Melinda (Universitas Malikussaleh, 2019)
Performance Appraisal is an effort to identify, measure (assess) and manage (management) to determine decisions about success or failure in carrying out work carried out by workers with work standards set by the company. Compensation for organizations / companies means rewards / rewards to workers who have contributed in realizing their goals, through activities called work. Total productivity is nothing but the ratio of what is produced (out put) to all what is used (in put) to obtain these results. FKIP-UISU Medan is part of one of the faculties at the Islamic University of North Sumatra Medan and its address at Jalan Puri Number 18 Simpang Jalan Alloy Tenaga Medan. The problem formulation is